EEG Changes During Reading in ADHD Children - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
The relation between electroencephalographic (EEG) findings, behavioral, and continuous performance test indicators were examined in 23 boys, aged 9-11 years, with attention deficit hyperactivity disorder (ADHD) and 23 matched controls in a study at the State University of New York, Cortland, NY, and University of Tennessee, Knoxville, TN.